Legal and social aspects of migrant employment in Turkey - Yildiz, Gaye Burcu (Z Problematyki Prawa Pracy i Polityki Socjalnej, 2022)
For over a decade, Turkey has been facing mass influx of Syrian citizens – besides Afghans, Iraqis, and Iranians – who are seeking international protection. This humanitarian problem has many different aspects, e.g., providing housing, employment, health services, and education. The general rule regarding the accommodation of refugees and asylum seekers is temporary accommodation centres. But this cannot be realised in the Syrian migrants’ case due to their massive numbers. Turkey is hosting 3,6 million Syrians under the temporary protection status. This international protection type does not give them the right to work per se. Like other foreigners who want to work in Turkey, Syrians have to apply for a work permit. In practice, many of the Syrians work informally, which causes major infringements of fundamental rights. Besides the legal aspect, this problem has to be handled by the cooperation of different fields of social sciences, especially by sociology and public policy. The implementation of legal instruments will not solve the social problems unless the integration of the migrants to the host community is realised with appropriate public incentives. This paper examines the national legislation concerning migrant workers. Following this examination, the author analyses the actual situation deriving from practice, based on prior research and reports of national and international organizations.